2013
DOI: 10.1111/1756-185x.12163
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center, observational study shows high proportion of Australian rheumatoid arthritis patients have inadequate disease control

Abstract: Cross-sectional assessment of this large cohort of Australian RA patients found a large proportion remain in moderate or high disease activity; suggesting a considerable evidence-practice gap. Improvement in disease control in this group may reduce future health burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…We determined that overall remission and LDA were achieved in half of the study sample. In two reports from a developed country, 8,9 the proportions of patients with MDA and HDA were lower than ours, but still quite high by 39% (number of study population=5,686) and 37.5% (number of study population=4,037), respectively. In a report on a multicenter study from Turkey that used the Turkish League Against Rheumatism RA registry data, 4 the overall proportion of patients with MDA and HDA was reported to be 68% (number of study population=2,539).…”
Section: Discussioncontrasting
confidence: 80%
“…We determined that overall remission and LDA were achieved in half of the study sample. In two reports from a developed country, 8,9 the proportions of patients with MDA and HDA were lower than ours, but still quite high by 39% (number of study population=5,686) and 37.5% (number of study population=4,037), respectively. In a report on a multicenter study from Turkey that used the Turkish League Against Rheumatism RA registry data, 4 the overall proportion of patients with MDA and HDA was reported to be 68% (number of study population=2,539).…”
Section: Discussioncontrasting
confidence: 80%
“…In a related note, a large cohort of Australian RA patients in a recent report spanning 11 years of observation, showed 40% achieving remission, but about 30% were noted to be in moderate disease activity despite access to tertiary care. They concluded that a considerable evidence–practice gap exists in their setting …”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted by the OPAL-QUMI using the clinical software program Audit4 (described previously) [7]. Deidentified data was sourced from 20 participating rheumatology practices comprising 42 rheumatologists across Australia.…”
Section: Methodsmentioning
confidence: 99%
“…The OPAL-QUMI (Optimising Patient outcomes in Australian rheumatoLogy-Quality Use of Medicines Initiative) consortium [7] is a point of care-derived observational registry database with clinical data recorded by Australian rheumatologists in real-time during routine clinical encounters. Cross-sectional data from OPAL has helped to provide insights into the reasons why a proportion of RA patients remain in moderate disease activity using a treat-to-target strategy [8].…”
Section: Introductionmentioning
confidence: 99%